2020
DOI: 10.1186/s12916-020-01771-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum B12 concentrations and mortality: experience in NHANES

Abstract: Background There is conflicting evidence in the literature on the association between (elevated) serum B12 concentrations and subsequent disease or mortality. We evaluated in the NHANES general population the association of serum B12 concentrations as well as vitamin B12 supplement intake with all-cause, cardiovascular, and cancer-related mortality, while taking into account demographic and lifestyle factors and significant other diseases which are known to be associated with poorer outcome. Methods The main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 65 publications
(86 reference statements)
0
37
1
1
Order By: Relevance
“…[87] Others have suggested that rather a daily oral dosage of 10 µg of B 12 is sufficient. [4] Despite the difference in numbers, supplementation is generally advised for individuals who consume a diet low in B 12 and may have a positive impact on public health [88] and possibly reduce the risk of developing cancer (but see above). [61] Although not commonly used, B 12 supplements can be administered nasally and sublingually as well.…”
Section: Mitigating and Preventative Treatmentsmentioning
confidence: 99%
“…[87] Others have suggested that rather a daily oral dosage of 10 µg of B 12 is sufficient. [4] Despite the difference in numbers, supplementation is generally advised for individuals who consume a diet low in B 12 and may have a positive impact on public health [88] and possibly reduce the risk of developing cancer (but see above). [61] Although not commonly used, B 12 supplements can be administered nasally and sublingually as well.…”
Section: Mitigating and Preventative Treatmentsmentioning
confidence: 99%
“…Concurrent validity of the NHANES 24 h diet assessment has been established through numerous studies. For example, results derived using the NHANES 24 h recall are predictive of non-alcoholic fatty liver disease [ 30 ], total mortality [ 31 ], cardiovascular mortality [ 32 ], cancer mortality [ 33 ], and coronary heart disease [ 34 ], to name a few.…”
Section: Methodsmentioning
confidence: 99%
“…In data from 24 262 participants with a mean age of 48.0 (SD, ± 19.0) years, Wolffenbuttel et al 130 found that low serum B 12 concentrations (< 140 pmol/L) were associated with a moderate increase in all causes of death (eg, chronic lower respiratory diseases, Alzheimer’s disease, influenza and pneumonia, cerebrovascular diseases, diabetes mellitus) and high serum concentrations of MMA and Hcy; the increase in cardiovascular causes of death was associated with both low (< 140 pmol/L) and high (> 700 pmol/L) serum B 12 levels.…”
Section: Effects Of Vitamin B 12 On Symptoms During and After Covid-19mentioning
confidence: 99%